Українська календарна гра у функціонально-генетичному аспекті - Макарець, Ольга; Makarets, Оlga (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті здійснено системний аналіз ігрового фольклору в українській усній народній творчості. Розглянуто теоретичні принципи, методологічні засади та історію вивчення питання української традиційної ігрової культури у фолькло- ристиці. Досліджено функції народної гри; запропоновано метод паралельного аналізу ознак і функцій ритуалу та гри як основних форм умовної поведінки. Визначено основні архетипні мотиви, які здійснюють інтеграцію ігрової тради- ції у вербальний та невербальний фольклор. Розроблено схему для визначення основних ігрових елементів, мотивів та ситуацій у жанрах фольклору.In the article the analysis of the systems of playing folklore isproduced in Ukrainian verbal folk work. Theoreticalprinciples, methodological bases and history of study of question of the Ukrainian traditional playing culture, areexamined in folklor. Essence and specific of theoretical дискурса of modern folkloristic open up round the phenomenon of game, universal parameters by means of that it is possible toclassify material and adequate to him to describe aredetermined, in this connection a few strategies of study ofgame were formed in due form and on maintenance andarray of the gamesphenomena (behavor, background, situation) that enter in the complement of game. Entered in the analytical field of Ukrainian folcloristic term a “playing culture” allows to connect to discourse ofplaying and entertaining culture all spheres of vital functionsof man. Genesis of folk game is investigated; the chart ofcomparative analysis of game and ritual is developed asbasic forms of conditional behavior. The aspects of exposureof distance are analysed between playing basis and folkloretext in the variety of their transformations and modifications.
The Ukrainian Calendar Playing a Functionally-genetic Aspect
Keywords: гра; ритуал; ігрова культура; ігрова ситуація; обрядова роль; мотив; game; ritual; playing culture; playing situation; ceremonial role; reason